PERBEDAAN GENESA MAGMA ANTARA TIN BEARING GRANITOID ROCKS DARI JALUR KEPULAUAN TIMAH INDONESIA DAN TIN BARREN GRANITOID ROCKS DARI PULAU BINTAN - Mesker H.J Dirk (Jurnal Geologi dan Sumberdaya Mineral, 2013)
There are differences between the granitoid rocks of the Menumbing- Bangka Island, Karimun Island, Kundur Island, with the granitoid rocks of the Bintan Island. The earlier are tin bearing granitoid rocks, while the later are tin barren granitoid rocks. The tin bearing granitoid rocks of Menumbing-Bangka Island, and Karimun and Kundur Islands, are strongly porphyritics, plagioclase as one of the primary rock forming minerals has composition of An0-20, the accessory minerals of ilmenite, zircon, apatite, secondary muscovite ± tourmaline ± flourite ± cassiterite ± monazite are found in the pegmatitic veins. The avarage content of SiO2 ≥ 70 wt%, CaO ≤ 2 wt%, and Na / (Na + K) ≤ 0.6. The tin bearing granitoid rocks are monzogranites, with calk-alkaline affinity, peraluminous, with increasing alkaline components to proportionally decreasing FeO* and MgO components. The age of the tin bearing granitoid rocks is around 211 ± 10 – 200 ± 4 my. or Upper Triassic, have formed from magma generated by melting of graywackce source material at a collision zone or convergence continental margins. The tin barren granitoid rocks of Bintan Island are weak porphyritic textures, plagioclase as one of the primary rock forming minerals has composition of An0-20, and hornblende as mafic mineral. The accessory minerals are magnetite, zircon, apatite, ± sphene. The avarage content of SiO2 ≥ 70 weight%, CaO ≤ 2 weight%, and Na / (Na + K) ≥ 0.6. The rocks are monzogranites and granodiorites, with calk-alkaline affinity, peraluminous, with increasing alkaline components to only decreasing FeO* component. The age of the tin barren granitoid rocks is around 230 ± 2 – 222 ± 3 my. or Middle Triassic – Upper Triassic, have formed at a subduction zone of magma generated from melting of mixed tholeiitic and equivalent graywacke source materials. In addition to those differences, both group of the granitoid rocks also differ in its magnetic susceptibility i.e. the tin bearing granitoid rocks have magnetic susceptibility around (0.18 – 0.90) S.I. unit, and the tin barren granitoid rocks around (2.75 – 7.75) S.I. unit.Keywords: Magma genesis, tin bearing granitoid rocks, Menumbing-Bangka Island, Karimun Island, Kundur Island, Bintan Island.